2011
DOI: 10.1029/2010jc006609
|View full text |Cite
|
Sign up to set email alerts
|

Revealing structural properties of the marine nanolayer from vibrational sum frequency generation spectra

Abstract: Natural nanolayers originating from sea surface and subsurface water samples collected in the Baltic Sea have been investigated using surface‐sensitive vibrational sum frequency generation (VSFG) spectroscopy. Distinct spectral signatures of CH and OH bond stretch vibrations have been detected at wavenumbers ranging from 2700 to 3900 cm−1. Measured water‐air interface spectra as well as observed signal intensity trends are discussed in terms of composition and structure of the natural organic nanolayer. Reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 78 publications
6
33
0
Order By: Relevance
“…For spectroscopy, the samples were poured into Teflon dishes measuring 14 cm in diameter and given a rest for at least 20 min prior to measurement to allow for equilibration between interface and aqueous phase. Details of the sampling procedure and consequences for the interpretation of the measured SFG signal intensity are outlined in our previous publications Laß and Friedrichs, 2011). Briefly, taking into account the sampling efficiency as well as the ratio of the areas of the field sampler and the spectrometer dish, our specific procedure yielded samples with a theoretical surface concentration of dry surfactants 12.5 times as high as on the original sea surface.…”
Section: Sampling Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…For spectroscopy, the samples were poured into Teflon dishes measuring 14 cm in diameter and given a rest for at least 20 min prior to measurement to allow for equilibration between interface and aqueous phase. Details of the sampling procedure and consequences for the interpretation of the measured SFG signal intensity are outlined in our previous publications Laß and Friedrichs, 2011). Briefly, taking into account the sampling efficiency as well as the ratio of the areas of the field sampler and the spectrometer dish, our specific procedure yielded samples with a theoretical surface concentration of dry surfactants 12.5 times as high as on the original sea surface.…”
Section: Sampling Methods and Proceduresmentioning
confidence: 99%
“…This study aims to show and interpret seasonal changes in amount and composition of the sea surface nanolayer at a coastal site in the southwestern Baltic Sea. Samples were analyzed with non-linear sum frequency generation spectroscopy, which has been quite recently established as a surface-specific tool for environmental ocean-air interfaces Laß and Friedrichs, 2011). Collected data serve as a step towards a more complete understanding of the state of the sea surface nanolayer in the course of the year, which is an important keystone for an improved parametrization of its role in the context of climate models.…”
Section: K Laß Et Al: Seasonal Signatures Of the Sea Surface Nanolayermentioning
confidence: 99%
“…Duplicate SML samples of about 50∼mL were collected on 8 days, transferred into polypropylene bottles and immediately frozen at −40 • C for transport and stored at −79 • C prior to analysis by vibrational sum-frequency generation (VSFG) spectroscopy using a commercial picosecond VSFG spectrometer (EKSPLA, 532 nm up-conversion) as described elsewhere (Laß and Friedrichs, 2011). The use of VSFG spectroscopy for environmental surfactant analysis has been introduced by Laß et al (2010) and the interpretation of the measured spectra in terms of surfactant abundance has been outlined and discussed in some detail in Laß and Friedrichs (2011) and Laß et al (2013). Non-linear VSFG provides surface-specific infrared spectra of the molecular nanolayer, i.e., the signal arises from the molecules residing directly at the interface.…”
Section: Surfactantsmentioning
confidence: 99%
“…PA is commonly used as a proxy for marine aerosols [41]. Lipopolysaccharides have been discovered both in the sea surface microlayer [42] and in atmospheric aerosol [43]. Facchini et al [43] found that sea water microgels, mainly composed of lipopolysaccharides, are preferentially transferred to the submicron aerosol size fraction during bubble bursting.…”
Section: Introductionmentioning
confidence: 99%